No resflor da idade: a velhice em Corpo de baile - HENRIQUE, Rosalina Albuquerque (Universidade Federal do Pará, 2024)
In this thesis, a discussion is proposed around the figurations of oldness based on the narratives of Corpo de baile (1956), Camilo, Cara-de-Bronze, Liodoro, Manuelzão and Rosalina, written by Guimarães Rosa (1908-1967), whose stories make us discuss about their human condition that remains unfinished when the evocation of the following discourse is marked: that the current old condition does not destine them to nothing. As opposed to this, they continue to feed feelings, desires and projects. When highlighting the importance of Guimarães Rosa’s literary production for the Brazilian literature scenario, some considerations about oldness (from yesterday to the third age of today) and its correlation with death will be noted. For this, the work is improved in bibliographical research, as in Beauvoir (2018), Ariès (2014), Elias (2001), Bosi (1994), Bolsanello, A.; Bolsanello, M. (1981), Kübler-Ross (1981, 1996), Debert (1988, 1999) and Cícero (2006, 2011), and also produced productions of students from Guimarães Rosa as Rónai (2020), Oliveira; Schröder (2020), Salles (2020), Leonel; Nascimento (2018), Diogo (2017), Mendonça (2013), Lucchese (2011), Ferraz (2010), Holanda (2009), Fantini (2008), Zilberman (2007), Xisto (1991), Brasil (1969), Ramos (1968), Candido (1964), Lins (1963), Secco (1994, 2003), Martins (1996, 2001), Passos (2000, 2007), Roncari (2007, 2008), Atroch (2013, 2017), Marchelli (2016, 2018), Nunes (1957, 1998, 2000, 2009) and Vasconcelos (1996, 1997, 1998). The theoretical scope is that of the Aesthetics of reception, proposed by Jauss (1994, 1982, 2002) through a hermeneutics addressed on the reader based on Gadamer (2002), in which the primary interest lies in the way the work of art should be received, taking into account the relationship between text and reader or even between effect and reception, without losing sight of the importance of the value and aesthetic experience of the work received and for those destined, assuming, in this sense, a new posture for the reader in which the literary work only exists when it is motivated by this subject, central to both aesthetic and historical knowledge. Finally, based on the aesthetic-recepcional method, discussions pertaining to oldness in Corpo de baile will be established: the relationship of the individual with time, the world and with his own history will be left aside.